Recent Progress on Gold-Nanocluster-Based Fluorescent Probe for Environmental Analysis and Biological Sensing - Mingxian Liu; Fenglin Tang; Zhengli Yang; Jing Xu; Xiupei Yang (Journal of Analytical Methods in Chemistry)
Gold nanoclusters (AuNCs) are one of metal nanoclusters, which play a pivotal role in the recent advances in the research of fluorescent probes for their fluorescence effect. They are favored by most researchers due to their strong stability in fluorescence and adjustability in fluorescence wavelength when compared to traditional organic fluorescent dyes. In this review, we introduce various synthesis strategies of gold-nanocluster-based fluorescent probes and summarize their application for environmental analysis and biological sensing. The use of gold-nanocluster-based fluorescent probes for the analysis of heavy metals and inorganic and organic pollutants is covered in the environmental analysis while biological labeling, imaging, and detection are presented in biological sensing.